Cover Image. (10th April 2018) - Tuleasca, C.; Najdenovska, E.; Régis, J.; Witjas, T.; Girard, N.; Champoudry, J.; Faouzi, M.; Thiran, J.‐P.; Bach Cuadra, M.; Levivier, M.; Van De Ville, D.
Abstract : The cover image, by C. Tuleasca et al., is based on the Original Article Pretherapeutic functional neuroimaging predicts tremor arrest after thalamotomy, DOI:10.1111/ane.12891 .